2012
DOI: 10.1161/atvbaha.111.234856
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of Differentiation-3 Mediates High Fat Diet-Induced Visceral Fat Expansion

Abstract: Objective Inhibitor of differentiation-3 (Id3) has been implicated in promoting angiogenesis, a key determinant of high fat diet (HFD)-induced visceral adiposity. Yet the role of Id3 in high fat diet (HFD)-induced angiogenesis and visceral adipose expansion is unknown. Methods and Results Id3−/− mice demonstrated a significant attenuation of HFD-induced visceral fat depot expansion compared to WT littermate controls. Importantly, unlike other Id proteins, loss of Id3 did not affect adipose depot size in youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 43 publications
2
50
1
Order By: Relevance
“…Further studies in Id3 −/− mice also did not reveal any significant changes in the metabolic phenotypes when they were fed a regular diet compared to wild-type mice. Nevertheless, when the mice were fed a HFD, expansion of visceral adipose depots was significantly reduced in Id3 −/− mice, whereas, such a reduction was not observed in other WAT locations (54). Accordingly, Id3 expression was more abundant in visceral compared to subcutaneous WAT, and Id3 expression was elevated in response to HFD only in visceral but not in subcutaneous adipose tissues of wild-type mice.…”
Section: Id Proteinsmentioning
confidence: 97%
See 2 more Smart Citations
“…Further studies in Id3 −/− mice also did not reveal any significant changes in the metabolic phenotypes when they were fed a regular diet compared to wild-type mice. Nevertheless, when the mice were fed a HFD, expansion of visceral adipose depots was significantly reduced in Id3 −/− mice, whereas, such a reduction was not observed in other WAT locations (54). Accordingly, Id3 expression was more abundant in visceral compared to subcutaneous WAT, and Id3 expression was elevated in response to HFD only in visceral but not in subcutaneous adipose tissues of wild-type mice.…”
Section: Id Proteinsmentioning
confidence: 97%
“…However, a recent study demonstrated that overexpression of Id3 did not result in any detectable changes in the expression of GLUT4, another marker of adipocyte differentiation. They also did not detect any significant differences in Oil-Red-O lipid staining between control and Id3-overexpressing cells or between wild-type and Id3 −/− MEFs that were induced to differentiate into adipocytes, suggesting that either overexpression or lack of Id3 did not alter the adipocyte differentiation program (54). Timing of analysis and the choice of adipocyte markers might have partially contributed to these conflicting observations in these two studies.…”
Section: Id Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Id3, on the other hand, has been shown to inhibit the transcription of the adiponectin gene, which encodes an adipocyte specific hormone whose levels are inversely correlated with obesity and insulin resistance and has protective effects against metabolic disorders (26). Id3 also promotes adipose tissue growth by facilitating angiogenesis through VEGF factor A expression (27). Id1 Ϫ/Ϫ mice have also been shown to have decreased body weight and fat mass (22).…”
Section: Id1 a Helix-loop-helix (Hlh) Protein That Inhibits The Funcmentioning
confidence: 99%
“…1 The authors first demonstrate that the inhibitor of differentiation-3 (Id3) is expressed in adipose tissue and induced during obesity. Fractionation and immunohistochemistry of the adipose tissue revealed that high-fat diet feeding and the ensuing development of obesity results in increased Id3 expression in endothelial cells.…”
Section: See Accompanying Article On Page 317mentioning
confidence: 99%